Cell death in cancer chemotherapy using taxanes - Xu, Ana P.; Xu, Lucy B.; Smith, Elizabeth R.; Fleishman, Joshua S.; Chen, Zhe-Sheng; Xu, Xiang-Xi (Frontiers in Pharmacology, 2024)
Cancer cells evolve to be refractory to the intrinsic programmed cell death mechanisms, which ensure cellular tissue homeostasis in physiological conditions. Chemotherapy using cytotoxic drugs seeks to eliminate cancer cells but spare non-cancerous host cells by exploring a likely subtle difference between malignant and benign cells. Presumably, chemotherapy agents achieve efficacy by triggering programmed cell death machineries in cancer cells. Currently, many major solid tumors are treated with chemotherapy composed of a combination of platinum agents and taxanes. Platinum agents, largely cis-platin, carboplatin, and oxaliplatin, are DNA damaging agents that covalently form DNA addicts, triggering DNA repair response pathways. Taxanes, including paclitaxel, docetaxel, and cabazitaxel, are microtubule stabilizing drugs which are often very effective in purging cancer cells in clinical settings. Generally, it is thought that the stabilization of microtubules by taxanes leads to mitotic arrest, mitotic catastrophe, and the triggering of apoptotic programmed cell death. However, the precise mechanism(s) of how mitotic arrest and catastrophe activate the caspase pathway has not been established. Here, we briefly review literature on the involvement of potential cell death mechanisms in cancer therapy. In particular, we discuss a newly recognized mechanism of cell death in taxane-treatment of cancer cells that involves micronucleation and the irreversible rupture of the nuclear membrane. Since cancer cells are commonly retarded in responding to programmed cell death signaling, stabilized microtubule bundle-induced micronucleation and nuclear membrane rupture, rather than triggering apoptosis, may be a key mechanism accounting for the success of taxanes as anti-cancer agents.